Consanguinity, genetic disorders and malformations in the Iranian population - Mokhtari, Roya; Bagga, Amrita (Acta Biologica Szegediensis, 2003)
The present study focuses on the effect of parental consanguinity on genetic disorders in the Iranian population, which is predominantly Muslim and where consanguineous marriages are quite common. Data were collected from three genetic centers from different areas of Tehran. Out of 800 affected subjects nearly 44% were born to consanguineous parents. While 37.8% of them were born out of parallel- cousin marriages, 28.9% were from cross- cousin alliances. Frequency of occurrence of genetic disorders was twice in children born to parallel-cousin parents as compared with those occurring out of cross-cousin marriages. Psychomotor retardation (14.3%), primary amenorrhoea (11.2%), and mental retardation (6.6%) topped the list of disorders encountered in children born to consanguineous parents. Cases of phenylketonuria were encountered exclusively in children of consanguineous couples. Of the patients having positive family history of genetic disorders, 93% had consanguineous parents. Two points emerge from the present study: that related parents, whatsoever the relationship, are more likely to have children with genetic defects; consanguineous couples who already have an affected child are 13 times more likely to have another affected child.